2008
DOI: 10.1080/09638280701532292
|View full text |Cite
|
Sign up to set email alerts
|

Organizing future research and intervention efforts on the impact and effects of gender differences on disability and rehabilitation: The usefulness of the International Classification of Functioning, Disability and Health (ICF)

Abstract: The International Classification of Functioning, Disability and Health (ICF) is discussed as being relevant to research and service delivery for women with disabilities. The personal meaning a disability has for a woman is shaped largely by Personal Factors. These, in turn, have historically been affected strongly by Environmental Factors such as culture and attitudes. Too often both Personal Factors, and how they are shaped by Environmental Factors, are not adequately addressed in our intervention programs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Pettersson et al saw in their study on electric wheelchair and scooter users that there were different needs among women and men [44]. Scherer and Dicowden [45] state that it is important to take gender and culture into consideration when it comes to technology and rehabilitation, and not allow women to be left behind. In our study, the self-identity of being an attractive woman was said to be difficult in a wheelchair.…”
Section: Discussionmentioning
confidence: 99%
“…Pettersson et al saw in their study on electric wheelchair and scooter users that there were different needs among women and men [44]. Scherer and Dicowden [45] state that it is important to take gender and culture into consideration when it comes to technology and rehabilitation, and not allow women to be left behind. In our study, the self-identity of being an attractive woman was said to be difficult in a wheelchair.…”
Section: Discussionmentioning
confidence: 99%
“…16 It is increasingly recognised that research and health interventions should include a focus on gender. [4][5][6]17,18 Although the International Classification of Functioning, Disability and Health 19 situates gender as a key feature of the environmental and personal context within which functioning and disability occurs, the complexity of personal factors, including gender, evade easy categorisation. 17,20,21 The predominance of white Caucasian men in SCI research is attributed to convenience sampling and epidemiological factors.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6]17,18 Although the International Classification of Functioning, Disability and Health 19 situates gender as a key feature of the environmental and personal context within which functioning and disability occurs, the complexity of personal factors, including gender, evade easy categorisation. 17,20,21 The predominance of white Caucasian men in SCI research is attributed to convenience sampling and epidemiological factors. 22 The possible dominance of male concerns in the SCI and health literature results from a combination of factors, including the gender imbalance in sex distribution of SCI, (3.8/1 male to female), 23 and a general tendency in health-care research to adopt a male norm 18,24 or gender neutral focus.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Scherer and DiCowden [23] performed a study on the use of the ICF in research and service provision for WwD: they concluded that ICF has an important practical application for evaluating interventions and they identified the use of the ICF as useful to recognise and emphasise more on Activities and Participation within interventions, suggesting that future research should focus more on the diverse social and psychological concerns of women.…”
Section: Implementation Of the Icf In Research On Women With Disabilimentioning
confidence: 99%
“…This report highlights national available data, source, year of collection and prevalence Furthermore, the proportion of WwD aged 16-64 is 15.6%: 3.1% of women between [16][17][18][19][20][21][22][23][24]8.4% between 25-54, and 18.8% between 55-64. These percentages are slightly lower than those of men with disabilities, who represent 16.2% of the total population: 3.6% in the age group [16][17][18][19][20][21][22][23][24]8.3% in group 25-54, and 22% in 55-64 range. The report stresses also the lack of a common data source and a time frame at European level for the collection of data on disability, underlined by the lack of a common definition of disability across Europe.…”
Section: Women With Disability: Prevalence From European and Internatmentioning
confidence: 99%